Pre-treatment of soy okara using multi-enzyme complex on sugar extraction and its effect on chemical composition, morphological structure, and antioxidant capacity - Lim, Siew Khim; Ahmad, Rosma; Mohamed, Mohd Shamzi; Ariff, Arbakariya; Tan, Joo Shun (Springer, 2021)
Purpose Okara is a highly perishable food processing by-product from soymilk and tofu manufacture. The present study aimed to optimize the pre-treatment of okara on the extraction of reducing sugars by applying a multi-enzyme complex, Viscozyme, containing a variety of carbohydrases to hydrolyze the okara cell walls. The chemical composition and the morphological structure of enzymatic-treated okara (ETO) were scrutinized.